An Analysis of Synonym in the Song Lyrics “Perfect” by Ed Sheeran: A Lexical Semantics Study - Santun Saniora Tamba; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study explores how synonymity is applied in the lyrics of Ed Sheeran's song